SISTEM PEMBUKA PINTU RUMAH MENGGUNAKAN HANDPHONE BERBASIS ARDUINO UNO DENGAN FASILITAS WI-FI - , ANZAR FAUZI, Drs.Abdul Rouf M.Ikom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
During this time in the open or lock the door using a key made , so it is usually in the house had few keys and each individual has the key . Mobile is an electronic tool that every person is almost always bring it wherever go , if used as a remote or mobile phone to access the door lock is certainly more efficient so that everyone in the house does not need to replicate nor require a key to open the door of the house . In this study created a prototype house that has a door and a mobile phone is used as a remote to unlock and lock the door . Webserver is used as an interface for sending commands . Gained command will be processed by the Arduino to turn on an electronic door lock in the open or locked condition . Mobile communication is used between the prototype using Wi - Fi . The results show that the locking system and door opener successfully created and can be remotely controlled through use of mobile phones , where the safety / padlock in the form of an electronic door lock that can lock and unlock the doors have opened and locked condition . To make access to the door of the only people who know the password and the IP address of the device that can lock and unlock it .